2010
DOI: 10.1111/j.1537-2995.2009.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Paired crossover study of two plateletpheresis systems concerning platelet product quality and donor comfort

Abstract: Only minor differences were observed despite the fact that the AC separators are run with two needles and the TA with one needle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…The second group of residual aggregates are characterized by their smaller size (<1 mm), often no more than the size of a pinhead, and are often referred to as microaggregates. They are less frequent, but when they occur, they may persist up to the end of storage . In some cases, depending on the standard operating procedure of the blood bank, these microaggregates may prevent the products from being released for transfusion and thus lead to product loss.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second group of residual aggregates are characterized by their smaller size (<1 mm), often no more than the size of a pinhead, and are often referred to as microaggregates. They are less frequent, but when they occur, they may persist up to the end of storage . In some cases, depending on the standard operating procedure of the blood bank, these microaggregates may prevent the products from being released for transfusion and thus lead to product loss.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Flesch et al . compared the two apheresis platforms Amicus and Trima Accel® (Terumo BCT) and found reversible micro‐ and macroscopically visible aggregates in 11% (10/91) of the Amicus and 1% (1/91) of the Trima, and 1/91 (1·1%) of irreversible aggregates in Amicus vs. 0/91 (0%) in Trima‐derived PLT concentrates. Similar results were reported by Skripchenko et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to these reports, the single-needle Amicus and single-needle Trima Accel have the highest CE and CR [3,8,9,10,58]. Flesch et al [21] reported that the double-needle Amicus and the single-needle Trima Accel showed similar platelet yields and donation times.…”
Section: Donor Screening For Plateletpheresismentioning
confidence: 99%